Evaluating the effects of extended cold ischemia on interstitial metabolite in grafts in kidney transplantation using microdialysis - Fonouni, Hamidreza; Jarahian, Parvin; Tahmasbi Rad, Morva; Golriz, Mohammad; Esmaeilzadeh, Majid; Hafezi, Mohammadreza; Macher-Göppinger, Stephan; Longerich, Thomas; Orakcioglu, Berk; Sakowitz, Oliver; Garoussi, Camelia; Mehrabi, Arianeb (Langenbeck's archives of surgery, 2013)
PurposeDuring kidney transplantation (KTx), the length of cold ischemia time (CIT) and the subsequent changes in energy metabolism may lead to variations in interstitial metabolites. Using microdialysis (MD), we evaluated the effects of a short and long CIT on changes of these metabolites.MethodsSixteen pigs were randomized in two identical groups, one with a short CIT and the other one with a long CIT. Using MD in the transplanted grafts, we evaluated the parenchyma concentrations of glucose, lactate, pyruvate, glutamate and glycerol in different stages.ResultsWe noted that during the warm ischemia time (WIT) and in the early post-reperfusion phase glucose levels increased more significantly in the long CIT group and remained high until the end of monitoring. At the end of CIT and during WIT, the long CIT group had a significantly higher glycerol level, but the level dropped gradually in the late post-reperfusion phase and reached a steady state in both groups.ConclusionsThe extended CIT clearly results in considerably impaired graft metabolism. The high interstitial glucose levels within hours after KTx could be considered as a marker of primary delayed function of the graft. Furthermore, the glycerol value could reflect the extent of graft injury during the ischemia time or in case of acute impairment of graft perfusion.
Published online: 16 October 2012
Gesehen am 11.04.2018